Magnetic and spectroscopic studies on molybdenum ions in CaF2-PbO-P2O5 glass system - Padma Rao, M. V. N. (Array, 2009)
Summary: CaF2-PbO-P2O5 glasses containing different mole fractions of MoO3 (ranging from 1.0 to 20 %) were prepared. Magnetic susceptibility, ESR and optical absorption, spectral studies on these glasses have been carried out. Interesting changes observed in these properties with the variation in the mole fraction of MoO3 have been discussed in the light of various oxidation states of molybdenum ions